A case of tuberculosis and black-grain eumycetoma co-infection in a non-endemic country: clinical presentation and therapeutic management. (November 2021) - Vu, Sonia; Belaube, Nicolas; Canestri, Ana; Develoux, Michel; Moreno, Alicia; Fourniols, Eric; Lê, Minh Patrick; Lassel, Ludovic; Pialoux, Gilles; Calin, Ruxandra
Highlights: Black-grain eumycetoma can present with co-existing tuberculosis. Treatment is challenging, with complex drug interactions and overlapping toxicity. Eumycetoma often requires surgical treatment and prolonged oral antifungal therapy. Abstract: We report a case of black-grain eumycetoma co-localized with Mycobacterium tuberculosis infection, presenting as a painless leg abscess and associated with vertebral tuberculosis. The rare association of these two pathogens raises several challenges regarding foreseeable drug interactions, side effects, the most appropriate management, and the potential link between these two diseases.